Thick section acrylonitrile rubber parts mechanical properties under compression and abrasive wear resistance - Velásquez-Restrepo, Sandra Milena; Giraldo-Vásquez, Diego Hernán; Zapata-Gallego, Natalia Trinidad (Universidad Pedagógica y Tecnológica de Colombia, 2015)
In this work the mechanical properties variability under uniaxial compression and the abrasive wear through the cross section of thick-piece carbon-black reinforced acrylonitrile rubber (NBR) parts, was studied. It has to take into account that in these type of pieces, the vulcanized rubber properties heterogeneity causes a variability effect, due to its low thermal diffusivity. Abrasive wear tests under dry conditions were carried out, seeking to identify the relationship between abrasive wear resistance and mechanical properties under uniaxial compression, such as hardness and elastic modulus. The samples in delivery state were evaluated after the vulcanization process, then environmentally exposed during three months and finally UV aged.Environmental aging stiffens the NBR, but the samples wear resistance from the cross sectional area center, is diminished. Their elastic modulus decreased with the UV aging, but its effect on the wear resistance depends from the previous environmental aging. Their hardness did not show a relationship neither with the elastic modulus nor with the wear resistance, therefore, it should not be used as a property to select the NBR rubbers, subject to wear resistance. The information obtained allows to generate design criteria for nitrile rubber-based parts.